2015
DOI: 10.1515/ntrev-2014-0050
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-enhanced photodetection in nanostructures

Abstract: Typical plasmonic nanostructures for the enhancement of photodetection in graphene and other semiconductor materials are reviewed. AbstractPhotodetection which converts the light into electric current, has significant importance in modern physics. For graphene photodetector, the performance is mainly limited by its low external quantum efficiency, mainly due to its poor light absorption properties. While for semiconductor photodetector, photocurrent generation is limited to photon energies above the band gap o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 87 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…However, due to their atomic thickness, the light-matter interaction in 2D materials is usually limited. On the contrary, plasmonics enable strong light-matter interaction with 2D materials due to high field concentration [135][136][137][138]. Additionally, it has been shown that surface plasmons in metallic nanoparticles can directly interact with 2D materials through hot electron injection [42,[139][140][141][142][143].…”
Section: Hot Electrons With 2d Materialsmentioning
confidence: 99%
“…However, due to their atomic thickness, the light-matter interaction in 2D materials is usually limited. On the contrary, plasmonics enable strong light-matter interaction with 2D materials due to high field concentration [135][136][137][138]. Additionally, it has been shown that surface plasmons in metallic nanoparticles can directly interact with 2D materials through hot electron injection [42,[139][140][141][142][143].…”
Section: Hot Electrons With 2d Materialsmentioning
confidence: 99%